Underwater acoustic signal acquisition based on optical interferometry in shallow water - Aliasghar Abniki; Hassan Sayyadi; Mohammad Saeed Seif (AUT Journal of Electrical Engineering)
Here, it is investigated the results of the implementation of an interferometric optical fiber acoustic sensor based on fiber Bragg grating (FBG). It is investigated the importance of different types of interferometer configurations as Michelson or Mach-Zehnder interferometers on the signal to noise ratio. It is also considered the role of polymer coating on the increasing of signal to noise ratio.  The results show the Michelson interferometer setup using polymer packaging causes an increasing signal to noise ratio. This latter configuration is used in a field set up in shallow water for acoustic signal detection in the range of 0.5-5 kHz. The goal of this paper is to extract acoustical signals using optical signals via optical sensors and demodulation methods.